Parameterizing the AGN Radius–Luminosity Relation from the Eigenvector 1 Viewpoint - Panda, Swayamtrupta (Frontiers in Astronomy and Space Sciences, 2022)
The study of the broad-line region (BLR) using reverberation mapping has allowed us to establish an empirical relation between the size of this line emitting region and the continuum luminosity that drives the line emission (i.e. the RBLR-L5100 relation). To realize its full potential, the intrinsic scatter in the RBLR-L5100 relation needs to be understood better. The mass accretion rate (or equivalently the Eddington ratio) plays a key role in addressing this problem. On the other hand, the Eigenvector 1 schema has helped to reveal an almost clear connection between the Eddington ratio and the strength of the optical FeII emission that originates from the BLR. This paper aims to reveal the connection between theoretical entities, like, the ionization parameter (U) and cloud mean density (nH) of the BLR, with physical observables obtained directly from the spectra, such as optical FeII strength (RFeII) that has shown immense potential to trace the accretion rate. We utilize the photoionization code CLOUDY and perform a suite of models to reveal the physical conditions in the low-ionization, dust-free, line emitting BLR. The key here is the focus on the recovery of the equivalent widths (EWs) for the two low-ionization emission lines - Hβ and the optical FeII, in addition to the ratio of their EWs, i.e., RFeII. We compare the spectral energy distributions of prototypical Population A and Population B sources, I Zw 1 and NGC 5548, respectively, in this study. The results from the photoionization modelling are then combined with existing reverberation mapped sources with observed RFeII estimates taken from the literature, allowing us to assess our analytical formulation to tie together the aforementioned quantities. The recovery of the correct physical conditions in the BLR then suggests that - the BLR ``sees'' only a very small fraction (~1-10%) of the original ionizing continuum.